Dampak Ideologi Liberalisme terhadap Pola Pikir Umat Islam - Rina Setyaningsih; Rohmawati Rohmawati; Vitaloka Vitaloka; Ainun Ni'mah; Ramdan Hadi; Siti Rahmadan Ningsih; Mei Andri Yani (Lembaga Pengembangan Kinerja Dosen, 2025)
Liberalism and Islamare two ways in different directions. Although both are often juxtaposed in every discussion of scholars, it is very difficult to put together. Islamis a religion that is assumed to the word of God through